Research into operational characteristics of the lithium ion battery - Xiong, Manni (2014)
The continuous development of electronic technology promote the development of a variety of electronic products to be miniaturization, such as a portable phone, micro cameras, laptops, etc. Lithium ion battery plays an significant way in the development of the science. But there is a big problem that how to ensure the safety of the batteries, which concern the personal security and the safety of property.